Tanggungjawab Pendidik Memelihara Kecerdasan Peserta Didiknya - Yazidul Busthomi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The way educators maintain the emotional intelligence of their students is as follows: 1) giving group assignments outside the school environment, 2) involving students in social activities, 3) the teacher's role model approach. The way educators maintain the spiritual intelligence of their students is by guiding, introducing and bringing their students closer to religious rituals, such as: 1. Performing the Duha prayer in congregation at the mosque in the madrasa environment, 2. Reading the Qur'an with tartil after the duha prayer at the mosque in the madrasa environment 3. Performing the noon prayer in congregation at the mosque in the madrasa environment. Broadly speaking, the responsibility of an educator is to maintain the intelligence that exists in each of his students. This intelligence must be nurtured so that students can grow and grow into intelligent human beings and are ready to face all challenges in the future. Among the intelligences that need to be nurtured by an educator are as follows: intellectual intelligence, emotional intelligence and spiritual intelligence.